Articulating tectonic: From iteration to nexus - Mochammad Mirza Yusuf Harahap (ARSNET, 2021)
This paper explores the articulation of tectonic as a potential basis for developing and understanding architectural programme in the context of architectural education. The piece delivers a reflective discussion that puts tectonic beyond the art of joining. Instead, tectonic, which informs the way material performs, insinuates a capacity in supporting the students to generate the spatial programme and atmospheric quality for the development of their architecture project. In particular, the study suggests the importance of tectonic articulation in generating the above spatialities. The study investigates such tectonic articulation by reflecting through a second-year design studio project in Universitas Indonesia, which focuses on developing dwellings designs driven by tectonic-based architectural design method. Through reflecting the students' projects this paper put forward three aspects of tectonic articulation, each of which explores the formal iteration, the tectonic-programme relationship, and the tectonic-atmosphere relationship. The study demonstrates contribution in understanding how tectonic is explored throughout the design process, informing multiple stages of design.